Um "mundo" de projetos culturais para jovens em periferias: violência, valores morais e pedagogias de intervenção - Lima, João Miguel Diógenes de Araújo (2014)
This research aims to understand the ways in which projects for youth in urban peripheries narrated by violence are organized and legitimized, in interactions with coordinators and participants of cultural projects in the neighborhoods of Greater Bom Jardim area in Fortaleza, Northeast Brazil. For over 20 years, cultural projects have been conducted as modes of pedagogical intervention among children and youth living in the outskirts of Brazilian cities. Proposed under the perspective of social vulnerability and violence prevention, cultural practices feature as means of transmission of moral and citizenship values. Accounts by youth considered successful are the most common showcase of such initiatives, spread by the media and, thus, understood in this analysis as “narratives of transformation”. In 2012, fieldwork focused on five cultural projects proposed by Greater Bom Jardim residents and awarded by a financing bid held by the Ministry of Culture and the National Program of Public Safety with Citizenship. In the everyday dynamics of projects, the relation between cultural practices and moral values among project coordinators and teachers became noticeable. Following these same agents in events and demonstrations against violence, connections among professional and institutions of the so-called “social field” stood out. In the course of two years, combining ethnography and research on the Internet, analysis focused on the ways in which agents, practices and institutions constitute a “world” of cultural projects for youth in peripheries. Coordinators help to legitimize this “world” as they construct visibility and reputations, social networks and the spread of moral values for youth. Questions emerged as the author took part in the implementation of a project in the same neighborhood. Furthermore, initiatives proposed by youth for youth were studied through participant observation, interview and the collective production of a zine, which enabled to encounter a positive perception of the notion of youth protagonism. A new generation of project coordinators is in the making as youth enroll in workshops for project elaboration and foster social networks with youth throughout town, which suggest the extension of these practices. Thus, as the “world” of cultural projects for youth in peripheries is consolidated and its support mechanisms become more complex, paradoxes arise and contribute with relevant questions for the ways projects and public policies for youth are monitored and evaluated.